2014
DOI: 10.1080/00288233.2013.863785
|View full text |Cite
|
Sign up to set email alerts
|

Botanical survey of perennial ryegrass-based dairy pastures in three regions of New Zealand: implications for ryegrass persistence

Abstract: A botanical survey of 24 commercial dairy pastures ranging in post-sowing age and perennial ryegrass type (mid-season diploid, late-season diploid, tetraploid) was undertaken in each of Waikato-Bay of Plenty (BoP), Taranaki and Canterbury during autumn/winter. The mean perennial ryegrass proportion (85% of total DM) and tiller density (3252 m −2 ) was greatest in Canterbury and the broadleaved weed proportion lowest (2%). Conversely, Waikato-BoP had the lowest ryegrass proportion (59%), tiller density (1817 m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 29 publications
6
26
2
Order By: Relevance
“…Our findings regarding regional persistence issues are consistent with those published by Tozer et al. (), who undertook an ex post approach to “fast track” persistence outcomes and sampled survivor perennial ryegrass plants from paddocks of different age classes to generate a time contrast. Their survey was carried out in three regions of New Zealand, and they also reported improved pasture sward persistence in Canterbury compared with the upper North Island, likely due to irrigation and also greater herbicide use to control broadleaved weeds.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings regarding regional persistence issues are consistent with those published by Tozer et al. (), who undertook an ex post approach to “fast track” persistence outcomes and sampled survivor perennial ryegrass plants from paddocks of different age classes to generate a time contrast. Their survey was carried out in three regions of New Zealand, and they also reported improved pasture sward persistence in Canterbury compared with the upper North Island, likely due to irrigation and also greater herbicide use to control broadleaved weeds.…”
Section: Discussionsupporting
confidence: 89%
“…Lower tiller densities in pastures sown with tetraploid cultivars rather than diploid are consistent with other studies (Orr et al 2005;Tozer et al 2014). However, there were no significant differences in tiller densities on other occasions and the trends in renewal effect (Fig.…”
Section: Impacts Of Renewal On Pasture Composition and Invertebratessupporting
confidence: 91%
“…Perennial ryegrass densities reported here are typical of those reported in other New Zealand studies but are lower than those of pastures reported in Europe. For example, compare Laidlaw (2004) who reported densities of 6370 tillers m -2 under a cutting regime (averaged over six diploid and three tetraploid cultivars) and Tozer et al (2014) who reported densities of 3030 tillers m −2 (averaged over 24 grazed dairy pastures of which 18 were sown with diploid and six with tetraploid cultivars). Lower perennial ryegrass tiller densities are associated Pasture renewal on Bay of Plenty and Waikato dairy farms 253 with poorer performance (Stewart & Hayes 2011) due to impacts on ryegrass population biology (Korte et al 1985) and are also consistent with the concerns expressed by farmers regarding poor pasture persistence in Waikato and Bay of Plenty (Kelly et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In New Zealand, dairy pastures mostly consist of a dominant perennial ryegrass component (Lolium perenne L.) combined with white clover (Trifolium repens L.) that contributes typically less than 20% of total annual yield (Tozer et al, 2014). In New Zealand, dairy pastures mostly consist of a dominant perennial ryegrass component (Lolium perenne L.) combined with white clover (Trifolium repens L.) that contributes typically less than 20% of total annual yield (Tozer et al, 2014).…”
Section: Introductionmentioning
confidence: 99%